On the viability of Mg extraction in MgMoN2: a combined experimental and theoretical approach. Issue 38 (25th September 2017) - Verrelli, R.; Arroyo-de-Dompablo, M. E.; Tchitchekova, D.; Black, A. P.; Frontera, C.; Fuertes, A.; Palacin, M. R.
Abstract : Extraction of magnesium from MgMoN2 was attempted by different methods but the migration barriers were found to be too high. Abstract : Layered MgMoN2 was prepared by solid state reaction at high temperature between Mo and Mg3 N2 in N2 which represents a simple synthetic pathway compared to the previously reported method that used NaN3 as the nitrogen source. The crystal structure of MgMoN2 was studied by synchrotron X-ray and neutron powder diffraction. The feasibility of oxidizing this compound and concomitantly extracting magnesium from the structure was assessed by both chemical and electrochemical approaches, using different protocols. The X-ray diffraction patterns of the oxidized samples do not exhibit any relevant difference with respect to that of the as prepared MgMoN2 and no differences in the cell parameters are deduced from Rietveld refinements. No hints pointing at the presence of any amorphous phase are observed either. These results are rationalized through DFT calculated energy barriers for Mg 2+ ion migration in MgMoN2 .